Legal status of zombie companies in Indonesia - Nurhilmiyah Nurhilmiyah (Indonesian Journal Education, 2026)
Zombie companies—persistently unprofitable firms sustained by cheap credit or government support—pose a significant challenge to Indonesia’s post-COVID-19 economic recovery. This study analyzes their legal status within Indonesian law, particularly in relation to the going concern principle, bankruptcy provisions, and state intervention policies. Using a normative-empirical approach, the research examines key regulations, including Law No. 40/2007 on Limited Liability Companies, Law No. 37/2004 on Bankruptcy as amended by Law No. 4/2023, and OJK regulations on credit restructuring. Findings reveal regulatory gaps that enable the persistence of zombie firms, leading to moral hazard, inefficient capital allocation, and rising non-performing loans (NPLs). Comparative insights from China highlight the importance of stricter enforcement and structured firm exit mechanisms. This study recommends establishing objective zombie thresholds, strengthening OJK oversight, and reforming legal frameworks to enhance market discipline and support sustainable economic growth in emerging economies.